People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2002 Article IV Consultation Discussions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation for Hong Kong Special Administrative Region highlights that a recovery from the Asian crisis started in 1999, and GDP growth surged to 10 1\2 percent in 2000. However, before sustained growth could take hold, the global slowdown in 2001 dealt another blow to the economy, and real GDP growth dropped to almost zero. Although the renewed downturn was led by falling exports, domestic demand also slowed. The outlook for 2002 is for a moderate recovery, spurred by the expected rebound in global activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet